TINGKAT KEPUASAN ANGGOTA TERHADAP PERAN KELOMPOK TANI DALAM PENGEMBANGAN USAHATANI AGROFORESTRI - Idin Saepudin Ruhimat (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2019)
The effectiveness of farmer groups in developing sustainable agroforestry farming requires the active participation of all members of farmer groups. One of the factors that influences the level of member participation in farmer group activities is the level of member satisfaction at the role of farmer group. This study aims to determine the level of member satisfaction and the main factors that influences increasing member satisfaction at the role of farmer group. The study was conducted in Cukangkawung Village, Sodonghilir Sub-district, Tasikmalaya Regency, West Java Province from November 2017 until April 2018. Data were analyzed using Customer Satisfaction Index and Importance Performance Analysis approaches. The results showed that the level of member satisfaction at the role of farmer groups in the development of agroforestry farming was still low. The main factors that need to be considered by farmer groups to increase member satisfaction with the role of farmer groups are the ability to increase members’ capacity, to establish cooperation with stakeholders, and to strengthen of farming capital. Therefore, it is recommended that the farmer group, central and local governments altogether should manage these main factors in developing agroforestry farming.